Manajemen Kelas Inklusif sebagai Fondasi Pembelajaran Matematika Efektif : Analisis Strategi Pengelolaan Kelas - Eric Dwi Putra; Hilda Ayu Sekar Arum; Sefy Wansita Putri; Slamet Slamet (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Classroom management is a fundamental aspect in creating a conducive learning environment, especially in mathematics learning in inclusive education. This study analyzes classroom management practices by 10th grade mathematics teachers at SMK Trunojoyo Jember, and their impact on learning engagement and effectiveness. The study used a qualitative descriptive method with a case study approach. Data collection was conducted through five days of observation, semi-structured interviews with teachers and students, and documentation studies. The results showed that the implementation of classroom management strategies such as U-shaped seating arrangements, humanistic communication, collaborative learning, and gamification-based positive reinforcement significantly increased student participation, from 25% to 75% of active groups. The implementation of peer support and individual learning adaptations also increased accessibility and engagement of students with special needs. Despite infrastructure limitations, teacher creativity and professionalism play an important role in maintaining learning effectiveness. This study concluded that adaptive, inclusive, and positive communication-based classroom management contributes to increased student motivation, participation, and mathematics learning outcomes.